2020
DOI: 10.1016/j.mechmat.2020.103451
|View full text |Cite
|
Sign up to set email alerts
|

On the effect of detwinning-induced plasticity in compressive cyclic loading of NiTi shape memory alloys

Abstract: A new inelastic mechanism, detwinning-induced plasticity (DIP), is proposed to model the response of NiTi SMAs to cyclic loading, based on thermodynamic considerations. DIP is incorporated into a constitutive framework for NiTi SMA. The constitutive framework also includes well-established inelastic mechanisms of phase transformation, transformation-induced plasticity, residual martensite, and detwinning. The model is constructed at the single crystal scale using the framework of thermodynamics and a crystal p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 43 publications
2
8
0
Order By: Relevance
“…The velocity gradient tensor, L , can also be divided into elastic, e L , and inelastic, p L , parts (Dhala et al, 2019;Erdle and Böhlke, 2017;Fohrmeister et al, 2019): Due to experimentally observed accumulation of residual martensite (Kang et al, 2009), the volume fraction of each martensite variant can be divided into the reversible, rev   , and the irreversible, ire   , volume fractions. The total volume fraction of martensite is considered as the sum of eversible and irreversible parts (Ebrahimi et al, 2020).…”
Section: Definition Of Various Deformation Mechanisms In the Framework Of Thermodynamicsmentioning
confidence: 99%
See 3 more Smart Citations
“…The velocity gradient tensor, L , can also be divided into elastic, e L , and inelastic, p L , parts (Dhala et al, 2019;Erdle and Böhlke, 2017;Fohrmeister et al, 2019): Due to experimentally observed accumulation of residual martensite (Kang et al, 2009), the volume fraction of each martensite variant can be divided into the reversible, rev   , and the irreversible, ire   , volume fractions. The total volume fraction of martensite is considered as the sum of eversible and irreversible parts (Ebrahimi et al, 2020).…”
Section: Definition Of Various Deformation Mechanisms In the Framework Of Thermodynamicsmentioning
confidence: 99%
“…Consequently, some habit plane variants (HPVs) will be formed. Each HPV is composed of two lattice correspondent variants (LCVs) or sub-variants (Ebrahimi et al, 2020;Yu et al, 2014). The stress-induced movement of interfaces between sub-variants is called detwinning (Thamburaja, 2005).…”
Section: Definition Of Various Deformation Mechanisms In the Framework Of Thermodynamicsmentioning
confidence: 99%
See 2 more Smart Citations
“…In practice, the cyclic loading-unloading of SMAs introduces a small amount of plastic strain which accumulates during the process. This process affects the SDC of the alloy, increases the peak stress during strain-controlled cycling [ 29 , 30 , 31 ] and influences the fatigue [ 32 ] and low cycle fatigue [ 33 ] of SMAs. This effect on fatigue confirms the role of dislocation storage as a damage accumulation effect.…”
Section: Introductionmentioning
confidence: 99%